Blood T-cell Vβ transcriptome in melanoma patients - Degauque, Nicolas; Schadendorf, Dirk (International journal of cancer, 2004)
Tumor-cells have been shown to elicit MHC-restricted and antigen-specific T-cell responses. In this article, we used a new approach to study T-cell responses in tumor-bearing patients based on a global representation of the Vβ-transcriptome, making it possible to grade CDR3-length distribution (CDR3-LD) alterations. Six patients with advanced melanoma disease, from whom blood samples were taken before and serially after tyrosinase-A peptide vaccination, were studied. The PBMC from patients displayed highly significant Vβ transcriptome alterations as compared to healthy individuals. Similar Vβ alterations could be detected both in PBMCs and at the tumor site. After vaccination, Vβ alterations could also be observed by gauging individually their transcript level but not their cell-surface expression. Some Vβ families exhibited high Vβ/HPRT transcript ratios (e.g., Vβ1), which represented up to 44% of the whole transcriptome, a situation that was not reflected by an increase in the percentage of T cells that expressed the corresponding protein and was not observed in normal individuals. In several instances, CDR3-LD altered T cells exhibited MHC-restricted and tumor-specific IFNγ or GM-CSF production. Finally, we show that the presence of a tumor and probably vaccination can affect Vβ transcriptome patterns and induce specific clones reactive to autologous tumor or vaccinating peptides. In combination with other methods, such an approach should help in identifying the clones actually involved in the response against the tumor.
Gesehen am 25.11.2020